Calculating the Individual Expenses of Foreign Tourists in West Nusa Tenggara - Muhammad Azizurrohman; Putrawan Habibi; Muhammad Ali; Rizky Angga Pramuja; Supiandi Supiandi; Faiza Husnayeni Nahar (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2022)
Purpose: The purpose of this article is to investigate local tourism demand, specifically in West Nusa Tenggara Province. Unlike other studies that focus on the number of tourists who arrive, this article seeks to delve deeper into individual foreign tourist expenditures in West Nusa Tenggara. Method: Using qualitative research methods and a questionnaire as a tool. This study is involving 50 respondents using a random sampling technique. Result: The author discovers that visitor spending may be divided into various categories, including hotels, food and beverages, souvenirs, travel agencies, and local transportation. In addition, foreign visitors' spending in NTB ranges from IDR 250 thousand to IDR 125 million per trip. The average cost per person in Indonesia is IDR 5 million. The lowest daily spend per person is IDR 9,400, while the highest is IDR 11 million. Contribution: This study provides information on the actual spending of individual foreign tourists considering that the data available at institutions such as the Central Statistics Agency or the local Tourism Office has not been able to provide the latest data.